Program Pendampingan dan Pemberdayaan Kelompok Masyarakat pada Komunitas Tuli Peduli Bitung (Kaleb) - Pranata Putra, Onky; Karim , Qadri; Alam, Syamsul; Ilda, Nildawati; Basri, Syahrul; Amansyah, Munawir; Ibrahim, Hasbi; Habibi (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2022)
The activities of mentoring and empowering community groups in the Bitung Deaf and Caring Community (KALEB) aim to develop the potential of persons with disabilities (deaf) to get opportunities for self-actualization and increase self-confidence. This activity began with the provision of hearing aids, followed by the provision of sign language learning books. Furthermore, there is assistance in processing inorganic waste for all KALEB members, processing organic waste as a craft object for the deaf community. Other activities include the establishment of literacy cafes, screen printing and sign language education. The results of the mentoring and empowerment of community groups in the Bitung Deaf Care Community (KALEB) gave rise to a glimmer of hope to all KALEB participants that they too are part of the community. KALEB participants rose from mental retardation and lack of confidence. Support for hearing aids, procurement of sign language learning books, sign language education programs, and socio-economic programs have made it more convincing for deaf friends that they can actually be present in the midst of the general public.